Significance of the Melanocortin 1 and Endothelin B Receptors in Melanocyte Homeostasis and Prevention of Sun-Induced Genotoxicity - Swope, Viki B.; Abdel-Malek, Zalfa A. (Frontiers in Genetics, 2016)
The membrane bound melanocortin 1 receptor (MC1R), and the endothelin B receptor (ENDBR) are two G-protein coupled receptors that play important roles in constitutive regulation of melanocytes and their response to ultraviolet radiation (UVR), the main etiological factor for melanoma. The human MC1R is a Gs protein-coupled receptor, which is activated by its agonists α-melanocyte stimulating hormone (α-melanocortin; α-MSH) and adrenocorticotropic hormone (ACTH). The ENDBR is a Gq coupled-receptor, which is activated by Endothelin (ET)-3 during embryonic development, and ET-1 postnatally. Pigmentation and the DNA repair capacity are two major factors that determine the risk for melanoma. Activation of the MC1R by its agonists stimulates the synthesis of eumelanin, the dark brown photoprotective pigment. In vitro studies showed that α-MSH and ET-1 interact synergistically in the presence of basic fibroblast growth factor to stimulate human melanocyte proliferation and melanogenesis, and to inhibit UVR-induced apoptosis. An important function of the MC1R is reduction of oxidative stress and activation of DNA repair pathways. The human MC1R is highly polymorphic, and MC1R variants, particularly those that cause loss of function of the expressed receptor, are associated with increased melanoma risk independently of pigmentation. These variants compromise the DNA repair and antioxidant capacities of human melanocytes. Recently, activation of ENDBR by ET-1 was reported to reduce the induction and enhance the repair of UVR-induced DNA photoproducts. We conclude that α-MSH and ET-1 and their cognate receptors MC1R and ENDBR reduce the risk for melanoma by maintaining genomic stability of melanocytes via modulating the DNA damage response to solar UVR. Elucidating the response of melanocytes to UVR should improve our understanding of the process of melanomagenesis, and lead to effective melanoma chemoprevention, as well as therapeutic strategies.